Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.


$$\begin{align} u(x,t)&=F(x+ct)+G(x-ct),\\ u(x,0)&=f(x),\\ u_t(x,0)&=g(x). \end{align}$$

How can I show that

$$\begin{align} F(x)&=\frac12f(x)+\frac1{2c}\int_{x_0}^xg(s)\,ds+C,\\ G(x)&=\frac12f(x)-\frac1{2c}\int_{x_0}^xg(s)\,ds+C\text{ ?} \end{align}$$

share|cite|improve this question

2 Answers 2

Hint: From the first three equalities you have

$$ f(x) = F(x) + G(x), $$

$$ g(x) = c\,\Bigl(F'(x)-G'(x)\Bigr). $$

Substitute these into the two expressions you have at the end.

share|cite|improve this answer
That should be $f(x) = F(x) + G(x)$. – Robert Israel Dec 3 '12 at 8:32
@RobertIsrael thanks. – Antonio Vargas Dec 3 '12 at 8:33
up vote 0 down vote accepted

I did the following:

$$ \begin{align} u(x,0)&=F(x)+G(x)=f(x),\\ u_x(x,0)&=F'(x)+G'(x)=f'(x),\\\\ u_t(x,t)&=cF'(x+ct)-cG'(x-ct),\\ u_t(x,0)&=F'(x)-G'(x)=\frac{1}{c}g(x),\\\\ u_x(x,0)+u_t(x,0)&=2F'(x)=f'(x)+\frac{1}{c}g(x),\\ &\Longrightarrow F'(x)=\frac{1}{2}f'(x)+\frac{1}{2c}g(x),\\ \int_{x_0}^{x}F'(s)\,ds&=\frac{1}{2}\int_{x_0}^{x}f'(s)\,ds+\frac{1}{2c}\int_{x_0}^{x}g(s)\,ds,\\ F(x)&=\frac{1}{2}f(x)+\frac{1}{2c}\int_{x_0}^{x}g(s)\,ds+C. \end{align} $$

Equation $G(x)$ can be derived similarly.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.